PROSPECTS FOR THE DEVELOPMENT OF 3D CONSTRUCTION AND ITS IMPACT ON THE ENVIRONMENTAL - Кірик, Катерина; Журавська, Наталія; Стефанович, Павло (SWorldJournal, 2023)
In this scientific work, the topic of development of advanced technologies for the construction of buildings with the help of 3D printing is highlighted. Positive and negative factors of traditional construction. Transition to eco-construction of world le